Motivasi Suami Terhadap Istri yang Mengalami Abortus Di Rsud Kota Padangsidimpuan - Heriansyah, Rizka; Dewi, Sri Sartika Sari (Jurnal Kesehatan Ilmiah Aufa Royhan, 2019)
Pregnancy is a very happy event for married couples, because pregnancy signifies that there will be an increase in family members, but the lack of support or motivation of a husband to his wife can be a cause for abortion. This is because the husband's support is an effort to pacify the wife's psychology in pregnancy, as well as the husband's motivation for the wife in dealing with abortion, it is important for the wife to experience an abortion and serves as a preventive strategy to reduce stress. This study aims to determine the motivation of husbands towards wives who experience abortion in Padangsidimpuan City Hospital. The population in this study were all husbands who experienced abortion, a sample of 30 people was taken by the method of consecutive sampling. The results showed the majority of husband's motivation with a good category of 27 people (90, 0%), enough knowledge of 3 people (10, 0% ). This illustrates that the motivation of the husband is in the good category where this situation is very influential with the motivation given by the husband to his wife. From the results of this study it is hoped that health workers will further improve the counseling and management of special prenatal class programs for mothers and their partners and carry out care involving the participation of the husband. From the results of this study are expected to improve information in conducting midwifery services about the need for motivation of husbands towards wives who experience abortion.